National Identity in the Textbooks of English as a Foreign Language - Vasilijević, Danijela; Semiz, Marina; Adžić, Branka (Zbornik radova Filozofskog fakulteta u Prištini, 2021)
Starting from the argument that foreign language teaching represents a suitable context for introducing national symbols of different countries, but also the learners’ own country, the role of textbooks of English as a foreign language in development and empowering the national identity of students in lower primary school was examined. With regards to different conceptualisations the national identity was operationalised in 11 categories: religion, customs and tradition, national feelings, language, symbols and features, solidarity and togetherness, cultural heritage, important people, geography terms, family and general information. The research was performed through the method of theoretic analysis and the method of content analysis. The units of analysis are: a) sentences of basic text in textbooks, b) sentences of additional information content, and c) image content. The research included English language textbooks for lower primary school licensed in the Republic of Serbia (N=12). Research results indicated that textbooks generally do not contribute to forming and empowering of national identity of students in lower primary school, especially with regards to categories: national feelings, historic subjects, language, family, solidarity, and togetherness.
Keywords: national identity; English language textbooks; global identity; content analysis; students of lower primary school